Generic Construction of Forward-Secure Revocable Identity-Based Signature and Lattice-Based Instantiations - He, Yan; Qin, Baodong; Gao, Wen; Zheng, Dong; Zhao, Qianqian (Security and communication networks, 2022)
Forward-secure revocation is a powerful cryptographic technique to alleviate key exposure attacks on identity-based cryptosystems. In recent years, quantum computers have made some breakthroughs, so in the foreseeable future, existing cryptographic systems will be subject to quantum attacks. However, known forward-secure revocable identity-based signature (FS-RIBS) schemes were designed over bilinear pairing groups and may suffer from quantum computing attacks. To address this issue, this paper proposes a generic method to construct FS-RIBS schemes, taking (hierarchical) IBS schemes as a basic component. By instantiating it with some post-quantum (hierarchical) IBS schemes, e.g., lattice-based (hierarchical) IBS, we immediately obtain six FS-RIBS schemes under the hardness of the small integer solution problem, which is secure against quantum computing attacks.